TRANSFORMATION OF APPROACHES TO STRATEGIC MANAGEMENT OF REMOTE WORK IN AN ORGANIZATION UNDER CONDITIONS OF MILITARY AGGRESSION - Ковальчук, Світлана; Настащук, Олег (SWorldJournal, 2026)
The article examines the transformation of approaches to strategic management of remote work in organizations under the conditions of military aggression against Ukraine. It is substantiated that the full-scale war has significantly changed the role of r